Lipids in Aspergillus flavus-maize interaction - Reverberi, Massimo; scarpari, marzia; camera, emanuela; ludovici, matteo; nobili, chiara; punelli, marta; zaccaria, marco; scala, valeria; fanelli, corrado; fabbri, anna a. (Frontiers in Microbiology, 2014)
In sSome filamentous fungi, the pathways related to the oxidative stress and oxylipins production are involved both in the process of host-recognition of the host that and in the pathogenic phase. In fact, recent studies have shown that the production of oxylipins in filamentous fungi, yeasts and chromists is also related to the development of the organism itself and to mechanisms of communication with the host at the cellular level. The oxylipins, also involved produced in by the host during defense reactions, are able to induce sporulation and to modulate regulate the biosynthesis of mycotoxins in numerous several pathogenic fungi, apparently replacing the endogenous ones. In A. flavus, the oxylipins play a crucial role as signals for the regulation regulatingof the biosynthesis of aflatoxins, the conidiogenesis and the formation of sclerotia. To investigate the involvement of the an oxylipins based cross-talk into Z. mays and A. flavus interaction, we analyzed the oxylipins profile of the wild type strain and of three mutants of A. flavus that are deleted at the Aflox1 gene level also during maize kernel invasion; Aflox1 encodes for a manganese lipoxygenase. A lipidomic approach has been addressed through the use of LC-ToF-MS, followed by a statistical analysis of the principal components (PCA). The results showed the existence of a difference between the oxylipins profile generated by the WT and the mutants onto challenged maize. In relation to this, aflatoxin synthesis which is largely hampered in vitro, is intriguingly restored. These results highlight the important role of maize oxylipin in driving secondary metabolism in A. flavus.